Mouse Paternal RNAs Initiate a Pattern of Metabolic Disorders in a Line-Dependent Manner - Satir-Basaran, Guzide; Kianmehr, Leila; Mehmetbeyoglu, Ecmel; Korkmaz Bayram, Kezban; Memis, Mehmet; Yilmaz, Zeynep; Tufan, Esra; Taheri, Serpil; Kelestimur, Fahrettin; Rassoulzadegan, Minoo (Frontiers in Genetics, 2022)
A wide range of diseases result from environmental effects, and the levels of many native tran-scripts are altered. The alteration of non-coding RNAs (ncRNAs) and transmission of the varia-tion to the next generation is increasingly recognized as a marker of disease. However, the deter-mining signals and mechanisms of RNA induced heritability remain unclear. We performed functional tests with four different genotypes of mice maintained on a high-fat diet to trace the transfer of the obesity/diabetes phenotype to the next generation in order to detect common sig-nals. Two founders of four mouse lines (B6/D2 hybrid and Dnmt2-/-C57BL/6) resist and do not change their phenotype while their sperm RNAs after microinjection into fertilized mouse eggs transfer the newly acquired phenotypes in a susceptible inbred line (C57BL6 or Balb/c). Unexpectedly in the same line of experiments, sperm RNA from animals raised on a normal diet when mixed with the sperm RNA from animals raised on a diet high in fat or synthetic miR-19b (inducer of obesity) affects or prevents the development of obesity and diabetes. However, it remains unclear what happens to ncRNAs signaling under diet. With a comprehensive new analysis of the stable tran-scripts maintained as an RNA/DNA hybrid in sperm, we suggest that a fraction of the RNAs are stably attached to the genome. Thus, we propose, changes in the dynamics of ncRNAs retention on DNA by factors such as transcriptional variations or lack of adequate methylation could serve as molecular markers to trace these epigenetics events.